PERAN POLA ASUH AUTORITATIF DAN PEMANTAUAN DIRI TERHADAP INTENSITAS CINTA DALAM BERPACARAN PADA REMAJA AKHIR DI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Vita Sunarto; I Made Rustika (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2015)
Love intensity is an important element to build a commitment in a dating relationship. The success in building love intensity greatly influenced by someone’s experience with people around them included their parents. Authoritative parenting style that applied to their children influence their children’s love intensity in their relationship at late adolescent. Adolescent who has high self-monitoring increase their ability to adapt with social environment include to their boyfriend or girlfriend. The purpose of this research is to find out the role of authoritative parenting style and self-monitoring toward someone’s love intensity in a relationship at late adolescents in Faculty of Medicine Udayana University. Subjects in this research were 145 late adolescents who are dating in Faculty of Medicine Udayana University. The instruments in this research were love intensity scale, authoritative parenting style scale and self-monitoring scale. The result of multiple regression analysis shows R=0,307 (F=7,407; p<0,05) thus it can be stated that both authoritative parenting style and self-monitoring together contributes to love intensity in dating relationship. Determination coefficient = 0,094 which means the effective contribution of authoritative parenting style and self-monitoring to love intensity is 9,4%. The result of product moment correlation analysis shows correlation coefficient between authoritative parenting style and love intensity is 0,301 (p<0,05) which means that authoritative parenting style and love intensity have a positive correlation. While the result of product moment correlation analysis shows correlation coefficient between self-monitoring and love intensity is 0,154 (p<0,05) which means that self-monitoring and love intensity have a positive correlation. Keywords: love intensity, authoritative parenting style, self-monitoring, late adolescent